Virus-inspired biogenic delivery system for advancing cancer therapy - Di Sun; Hao Liang; Qianwen Mu; Chengchao Chu; Gang Liu; Chao Liu (Biomedical Technology)
Virus-inspired particles have been utilized in various applications, including vaccination, gene therapy, drug therapy, and diagnostics. Biogenic delivery systems imitating the natural structure of viruses are regarded as innovative nanoplatforms used to deliver drug compounds to related sites and target cells in organisms. Among them, the components comprised of virus-like particles (VLPs) derive from the proteins or peptides of the viruses; the glycoproteins on their surface exert significant function as specific targeting. Types of assembled glycoproteins and encapsulated drug molecules confer the complexity and varieties of structure, function, and treatment of VLPs. VLPs lack viral virulence, resulting from a viral genetic material deficiency. In vaccine research, Virus-mimic nanovesicles have been effectively verified against cancer via the immunogenicity and the pharmacological effect of drug molecules delivered to mediate an immune response in the body. This review summarizes the research status of virus-inspired drug delivery platforms for cancer therapy utilization.